2011
DOI: 10.1007/s10762-011-9839-9
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Ferroelectricity of a SrTiO3 Thin Film on a MgAl2O4 Substrate Observed by Terahertz Time-Domain Spectroscopy

Abstract: A SrTiO 3 thin film was deposited on a MgAl 2 O 4 (100) substrate with a 3.5 % larger lattice constant than that of the SrTiO 3 . The temperature dependence of the dielectric dispersion of the SrTiO 3 thin film was measured by terahertz time-domain spectroscopy, and the dielectric strength and soft-mode frequency showed positive and negative peaks at around 170 K, respectively. In addition, a deviation of the dielectric constant from the theoretical fitting curve in the gigahertz range and an increase in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[12][13][14] Terahertz spectroscopic data have been previously reported on STO films on various substrates (Refs. [4,5,8,11,[15][16][17][18]) with thicknesses as low as 17 nm, [4,16] but typically on the order of hundreds of nanometers. The capability of far-infrared and terahertz ellipsometry to detect the soft mode in STO thin films has already been demonstrated, [3,19] but so far no THz spectra were reported on ultrathin (∼ 10 nm) films.…”
mentioning
confidence: 99%
“…[12][13][14] Terahertz spectroscopic data have been previously reported on STO films on various substrates (Refs. [4,5,8,11,[15][16][17][18]) with thicknesses as low as 17 nm, [4,16] but typically on the order of hundreds of nanometers. The capability of far-infrared and terahertz ellipsometry to detect the soft mode in STO thin films has already been demonstrated, [3,19] but so far no THz spectra were reported on ultrathin (∼ 10 nm) films.…”
mentioning
confidence: 99%
“…In our previous study, we observed the dielectric dispersion of STO thin films on MgAl 2 O 4 (MAO) substrates with a lattice mismatch of +3.39%, which is much larger than the lattice mismatch of +0.99% between STO and DSO. The temperature dependence of the dielectric dispersion of a 360 nm thick STO film on MAO in the terahertz region showed signs of a ferroelectric phase transition at around 170 K, much lower than that expected from the lattice mismatch [10]. We concluded, therefore, that the strain in the STO thin film on MAO used in that experiment was somewhat relaxed, and sufficient strain required for the generation of ferroelectricity at room temperature was not induced in the film.…”
Section: Introductionmentioning
confidence: 65%